The challenge of writing histories of 'women': the case of women and the law in late medieval Ireland. Issue 170 (November 2022) - Booker, Sparky
Abstract: Critiques of women's history based on intersectional analysis have demonstrated the importance of recognising differences between women and the perils of assuming commonality of experience based on gender. The idea that we can treat women as a group in some meaningful way is further complicated in medieval legal history by the fact that women's legal entitlements differed depending on their marital status. This paper examines women's experiences of the law in the English colony in late medieval Ireland. It argues that, despite the importance of ethnicity, social status and marital status in shaping different women's experiences of the law, gender played a significant role in their legal arguments and the ways in which juries and justices perceived them. Women's experiences at law were influenced in myriad ways by shared societal assumptions about their vulnerability and subordination to men. These assumptions influenced women regardless of the many social divisions and circumstances that made each woman unique. This study finds, therefore, that 'women' is a legitimate and productive category for historical research in the late medieval legal context but urges historians to interrogate more robustly why 'women' is an appropriate analytical category for their specific historical questions.